Development and Relationships Between Phonological Awareness, Morphological Awareness and Word Reading in Spoken and Standard Arabic - Schiff, Rachel; Saiegh-Haddad, Elinor (Frontiers in Psychology, 2018)
This study addressed the development of and the relationship between foundational metalinguistic skills and word reading skills in Arabic diglossia. It compared Arabic-speaking children’s phonological awareness, morphological awareness, and voweled and unvoweled word reading skills in spoken and standard language varieties separately in children across five grade levels from childhood to adolescence. Second, it investigated whether skills developed in the spoken variety of Arabic predict reading in the standard variety. Results indicate that although individual differences between students in phonological awareness are eliminated towards the end of elementary school in both spoken and standard language varieties, gaps in morphological awareness and in reading skills persisted through junior and high school years. The results also show that the gap in reading accuracy and fluency between Spoken Arabic and Standard Arabic was evident in both voweled and unvoweled words. Finally, regression analyses showed that morphological awareness in Spoken Arabic contributed to reading fluency in Standard Arabic, i.e children’s early morphological awareness in spoken Arabic explained variance in children’s gains in reading fluency in standard Arabic. These findings have important theoretical and practical contributions for Arabic reading theory in general and they extend previous work regarding the cross-linguistic relevance of foundational metalinguistic skills in the first acquired language to reading in a second language, as in societal bilingualism contexts, or a second language variety, as in diglossic contexts.